Predictors of Life Satisfaction Among Older Adults in Siberia; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Didino D. Daniel; Frolova E. A. Elena Aleksandrovna; Taran Е. А. Ekaterina Aleksandrovna; Gorodetski K. Kristina (2016, 2016)
Title screen